Behavior of LNAPL in soils with multimodal pore-size distribution - Alfaro Soto, Miguel [UNESP] (2015)
New models are presented to characterize the behavior of light nonaqueous phase liquids (LNAPL) and determine their specific volume in soils with a multimodal distribution of pores making an adaptation of the information contained in the API4760 publication entitled LNAPL Distribution and Recovery Model (LDRM). The estimation of LNAPL requires information about the distribution of the non-mixable fluids under vertical equilibrium conditions, which include the effects of capillary forces in a system made up of subsystems with different distributions of pores, as well as the methods to be used for the prediction of the distribution of LNAPL as a function of thickness of the LNAPL in the monitoring well. Simulations with data from the specialized literature show that the utilization of a unimodal model in soils with such a pore distribution runs the risk of estimates of the total and recoverable volumes of LAPL differing in some 76%, resulting in erroneous estimates of the time required for the recuperation of conventional systems.